The allure of capitalism : an ethnography of management and the global economy in crisis - Røyrvik, Emil A. (Berghahn Books, 2011)
This is an extraordinary book, huge in every way, one man's personal synthesis of the world we live in, as seen through his own experience of Norway's largest business corporation and much much more. The book and the author have a lot going for them. There are few in-depth anthropological studies of global corporations. Scandinavian anthropology is enjoying a boom and this is reflected in the present study. The author is ... open to a very wide range of philosophy, critique, journalism, anthropology, and social science. Keith Hart, University of London. [T]his book is a gem. I like it very m.